Letramento literária no ensino fundamental por meio de letras da música popular brasileira - Santos, Gilvamarques Pereira dos (2016)
The music has become an important didactic resource to improve the teaching, helping the students to have access to a qualified formation. It is not very used by the didactic books, and when it is used, it is just to analyze gramma questions. The manuals that proposes to discuss deeply the themes in the lyrics are rare. We know that the student must recognize its poetical worth to have a significant interpretation of the composition, jump in its original country culture, at the time it was written and, mainly, in the transmitted ideas. This information are many times off the didactic books, it is, therefore, interesting that the study of these texts do not be limited to only these manuals to ensure relevant knowledge to the students. In this case, this work intend to develop a intervention project, through the reading and interpretation of both lyrics: Admirável gado novo, by Zé Ramalho and Vozes da seca, by Luiz Gonzaga and Zé Dantas, in Portuguese classes, in a 9th grade class of Fundamental School. The objective is to execute the comprehension of its constitutive, in order to provide a better vision of the world and a better cultural repertory for the students. Therefore, we will make a study about the lyrics in this work – the poetry. We will accomplish the theorist studies to reach the proposed finality, in order to support the importance of the literacy through the compositions. The authors that contributed for the development of our proposal was: Soares (2009) and Kleiman (2012) about the literacy definitions and its peculiarity; Cosso (2014), Abreu (2006) and Candido (2011) about the literary text approaches in class; Tinhorão (2010), Aguiar (1993) and Ribeiro Neto (2011), about the lyrics and poetry relation; Severiano (2013), about the identity and the popular brazilian music social context.